2011
DOI: 10.1103/physrevc.83.044319
|View full text |Cite
|
Sign up to set email alerts
|

Imprint of adiabatic structures in monopole excitations ofBe12

Abstract: The monopole excitations (0 + g.s. → 0 + ex ) of light neutron-excess systems 12 Be = α + α + 4N are investigated by the generalized two-center cluster model. We analyze the mechanism of an enhancement of the monopole strength in connection to structures of adiabatic energy surfaces as a function of an α-α distance. The crossing of two adiabatic energy surfaces, which have different intrinsic configurations, increases the monopole strength. Furthermore, we find that the monopole strength is strongly enhanced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 21 publications
(46 reference statements)
5
40
0
Order By: Relevance
“…[43]). The ISM strengths in Be isotopes have been theoretically studied by cluster models and suggested to be a good probe for cluster states [43][44][45]. One of the authors, Y. K-E., has studied the E1 and compressive ISD strengths of Be isotopes and discussed the dipole excitations for cluster states [46].…”
Section: Introductionmentioning
confidence: 99%
“…[43]). The ISM strengths in Be isotopes have been theoretically studied by cluster models and suggested to be a good probe for cluster states [43][44][45]. One of the authors, Y. K-E., has studied the E1 and compressive ISD strengths of Be isotopes and discussed the dipole excitations for cluster states [46].…”
Section: Introductionmentioning
confidence: 99%
“…This finding boosted the studies of the cluster states by using the monopole transition as a probe. In these days, various cluster states in stable and unstable nuclei [33][34][35][36][37][38][39][40] are discussed on the basis of their enhanced monopole strengths.…”
Section: Introductionmentioning
confidence: 99%
“…We have found that, in 10,14 Be, the ionic structures, which are embedded in continuum, are realized as the cluster's excitation modes from the bound states. In 16 Be, an energy level, which can be considered as the α+α analog state, is obtained in 16 Be.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, two resonant states, which have the ionic structures, are identifie by solving the 6 He+ 8 He collision. These resonant states correspond to the cluster's excitation modes from the bound states: The 0 + 3 state, which has the ionic structure of 6 In 10 Be, one of two 0 + states above the α threshold becomes a broad continuum state, but, in 14 Be, both unbound 0 + states becomes the resonant states. This is because of the increase of excess neutrons.…”
Section: Results Of Even Be Isotopesmentioning
confidence: 99%
See 1 more Smart Citation